Study participant reported outcomes of mental health interventions: results from a randomized controlled trial among survivors of systematic violence in southern Iraq. (15th May 2018) - Mahmooth, Z.; Weiss, W. M.; Zangana, G. A. S.; Bolton, P.
Abstract : Background: Common mental health problems experienced by survivors of systematic violence include trauma, depression, and anxiety. A trial of mental health interventions by community mental health workers for survivors of systematic violence in southern Iraq showed benefits from two psychotherapies on trauma, depression, anxiety, and function: Common Elements Treatment Approach (CETA) and cognitive processing therapy (CPT). This study assessed whether other non-predetermined changes reported by intervention participants were more common than in the control group. Methods: The trial involved 342 participants (CETA: 99 intervention, 50 control; CPT: 129 intervention, 64 control). Sixteen intervention-related changes since enrollment were identified from free-listing interviews of 15 early therapy completers. The changes were then added as a new quantitative module to the follow-up questionnaire. The changes were organized into eight groupings by thematic analysis – family, social standing, anger management, interest in regular activities, optimism, feeling close to God, avoiding smoking and drugs, and physical health. All participants were interviewed with this module and responses were compared between intervention and control participants. Results: Multi-level, multi-variate regression models showed CETA intervention subjects with significant, positive changes relative to CETA controls on most themes. CPT intervention subjects showed little to no change compared with CPT controls in most themes. Conclusions: Participants receiving CETA reported more positive changes from therapy compared with controls than did participants receiving CPT. This study suggests differential effects of psychotherapy beyond the predetermined clinical outcome measures and that identification of these effects should be part of intervention evaluations.